TRANSIENT MEASUREMENTS AT THE WALL-JET RING DISK ELECTRODE - Compton, R; Fisher, A; Latham, M; Brett, C; Brett, A (Kluwer Academic Publishers, 1992)
Theory is presented for the wall-jet ring disc electrode (WJRDE) which predicts the current transient at the ring resulting from a potential step at a WJRDE disc for the case where the ring is potentiostatted so as to reverse the reaction which occurs at the disc. The shape of such transients, in which double-layer charging effects are minimal, is revealed to be very sensitive to differences in the diffusion coefficient of the electroactive species which reacts at the disc and that of the corresponding product. Accordingly such measurements are recommended for the study of complex electrode processes in order to separate mass transport parameters (diffusion coefficients) from homogeneous kinetic phenomena. © 1992 Chapman and Hall.